2018
DOI: 10.1111/1754-9485.12741
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic study of tumour extension for clinically localized unilateral nasopharyngeal carcinoma: Should the contralateral side be included in the clinical target volume?

Abstract: Contralateral pharyngeal recess infiltration is rare in patients with clinically diagnosed unilateral primary NPC. Reduced CTV coverage, including the CPSW but not CRP, is feasible for patients with unilateral cancer of the nasopharynx without contralateral LN metastasis or positive EBV-DNA. Further large-sample studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, it should be noted that they used plain CT and an electronic nasopharyngoscopy to diagnose unilateral NPC. Li et al performed biopsies of the posterior wall of the contralateral pharyngeal roof as well as the contralateral pharyngeal crypt in 20 unilateral NPC cases judged by MRI [ 11 ]. Their result showed that five patients had subclinical lesions on the posterior wall of the contralateral pharyngeal roof and pharyngeal crypt biopsies were also positive for two patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that they used plain CT and an electronic nasopharyngoscopy to diagnose unilateral NPC. Li et al performed biopsies of the posterior wall of the contralateral pharyngeal roof as well as the contralateral pharyngeal crypt in 20 unilateral NPC cases judged by MRI [ 11 ]. Their result showed that five patients had subclinical lesions on the posterior wall of the contralateral pharyngeal roof and pharyngeal crypt biopsies were also positive for two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral NPCs constitute about 10% of all NPC cases [ 10 , 11 ]. At present, data are limited regarding the characteristics of locoregional extension of this subtype of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the cumulative incidence of tumor invasion, anatomical sites around the nasopharynx can be divided into 3 risk levels to evaluate the locoregional extension and failure patterns of NPC and then improve CTV delineation ( 39 , 40 ). The CTV can be reduced on the basis of the contralateral expansion of NPC in patients with unilateral tumors ( 41 ). Consensus guidelines on CTV definition include geometric expansion beyond the visible gross tumor volume ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…One area of active research is the selected sparing of the contralateral structures in patients presenting with unilateral disease. As the fossa of Rosenmüller is the most common site of origin, early NPC typically presents unilaterally and may remain so as the tumor advances, constituting approximately 10% of all NPC at presentation [ 8 , 9 ]. An endoscopic biopsy study has revealed a low incidence of occult microscopic disease in the contralateral nasopharyngeal mucosa in unilateral NPC which did not cross the midline [ 8 ].…”
Section: Target Delineationmentioning
confidence: 99%
“…As the fossa of Rosenmüller is the most common site of origin, early NPC typically presents unilaterally and may remain so as the tumor advances, constituting approximately 10% of all NPC at presentation [ 8 , 9 ]. An endoscopic biopsy study has revealed a low incidence of occult microscopic disease in the contralateral nasopharyngeal mucosa in unilateral NPC which did not cross the midline [ 8 ]. The risk of skipped discontinuous invasion to the contralateral parapharyngeal space and skull base is also exceedingly low in unilateral NPC, making unilateral irradiation an attractive option to reduce radiation side effects, such as trismus and xerostomia [ 10 ].…”
Section: Target Delineationmentioning
confidence: 99%